RANCANG BANGUN APLIKASI DETEKSI TEPI CITRA DIGITAL MENGGUNAKAN ALGORITMA PREWITT - Ardiansyah Putra; Volvo Sihombing; Mustafha Haris Munandar (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
Edge detection is one of the algorithms used in Digital Image Processing. This algorithm serves to identify the line/edge of the image object to highlight the boundary lines of the image information. Edge is a set of connected pixels (connected pixels) that restricts the objects contained in the image. Senses the eye is one that is used by humans to see. However, the human eye has its limitations in capturing the electromagnetic signals. Therefore, created a computer or imaging machine that can capture almost the entire signal elektromagnetic . Imaging machines can work with imagery from sources that do not fit, do not fit or can not be captured by human vision. This is why digital image processing have very wide usefulness. Image processing technology can fit into a variety of fields such as medicine, geology, marine , industrial and others.